Diabetes mellitus, metabolic syndrome, and sleep disorders: An underestimated relationship - Shital Patil; Sanidhaya Tak; Abdul Wahab Mirza (Annals of Medical Science and Research)
Diabetes mellitus (DM) is the most prevalent endocrine disorder globally. DM is under-evaluated and less efficiently managed in terms of ruling out comorbid conditions associated with it and predisposing factors resulting in poor outcomes. Sleep disorders are more common than usually diagnosed due to less awareness in the community regarding the importance of timely diagnosis and the impact of interventions related to proper sleep hygiene and sleep structure. Obstructive sleep apnea (OSA) is independently associated with cardiovascular and cardiometabolic risk in several large epidemiological studies. OSA leads to several physiological disturbances, such as intermittent hypoxia, sleep fragmentation, and an increase in autonomic tone. Metabolic syndrome (MS) is an adverse outcome that is typically associated with obesity. It is a cluster of metabolic risk factors for type 2 DM (T2DM) and cardiovascular diseases (CVDs), including central obesity, hypertension, hyperglycemia, insulin resistance, and dyslipidemia. T2DM is often associated with OSA, and a bidirectional relationship may exist between the two diseases, mediated by both weight- and physiology-dependent mechanisms. OSA is highly associated with T2DM, and treatment of OSA may have a positive impact on the cardiometabolic profile. In this review, we have attempted to summarize the impact of sleep disorders on MS and DM, and vice versa, with special emphasis on newer medical options in the management of DM and cardiometabolic syndrome.